The optimal hedge ratio and hedging effectiveness of stock index futures An empirical study of TAIEX index futures contract - Nguyen, Thi Mai Hanh (2014)
Throughout research literature on hedging with futures, a number of techniques to estimate the optimal hedge ratio that minimizes volatility of the hedged portfolio returns have been proposed. While these techniques hold theoretical appeal, there has not consistent evidence of which the most appropriate hedging technique is. This study, using the futures contract on the Taiwan’s TAIEX total returns index, provides an empirical comparison of three different econometric techniques. Specifically, the conventional OLS regression model, the VECM, and the bivariate DCC-GARCH model are estimated, performance of which are compared among each other and with the naïve hedge to determine the best hedging strategy. Hedging effectiveness is evaluated in terms of in-sample and out-of-sample returns variance minimization, under three short-term hedging horizons. This study concludes that despite simplicity in estimation, the constant hedge ratio estimated by the OLS regression is the most reliable and effective hedging strategy for TAIEX index short-term investors. Nevertheless, under the highly volatile market condition experienced during the global financial crisis 2008-2009, a dynamic hedging strategy is favored.